Motor Rhythm Dissection From the Backward Circuit in C. elegans - Yu, Bin; Wang, Ya; Gao, Shangbang (Frontiers in Molecular Neuroscience, 2022)
Motor rhythm is initiated and sustained by oscillatory neuronal activity. We recently discovered that the A-class excitatory motor neurons (MNs) (A-MNs) function as intrinsic oscillators. They drive backward locomotion by generating rhythmic postsynaptic currents (rPSCs) in body wall muscles. Molecular underpinning of the rPSCs, however, is not fully elucidated. We report here that there are three types of the rPSC patterns, namely the phasic, tonic, and long-lasting, each with distinct kinetics and channel-dependence. The Na+ leak channel is required for all rPSC patterns. The tonic rPSCs exhibit strong dependence on the high-voltage-gated Ca2+ channels. Three K+ channels, the BK-type Ca2+-activated K+ channel, Na+-activated K+ channel, and voltage-gated K+ channel (Kv4), primarily inhibit tonic and long-lasting rPSCs with varying degrees and preferences. The elaborate regulation of rPSCs by different channels, through increasing or decreasing the rPSCs frequency and/or charge, correlates with the changes in the reversal velocity for respective channel mutants. The molecular dissection of different A-MNs-rPSC components therefore reveals different mechanisms for multiplex motor rhythm.